Effectiveness of a novel, automated telephone intervention on time to hospitalisation in patients with COPD: A randomised controlled trial. (April 2020) - Sink, Eric; Patel, Kunjan; Groenendyk, Jacob; Peters, Robert; Som, Avik; Kim, Ellen; Xing, Maggie; Blanchard, Melvin; Ross, Will
Introduction: Owing to its capacity to perform remote assessments, telemedicine is rising as a new force in chronic obstructive pulmonary disease (COPD) management. We conducted an eight month randomised-controlled-trial to study the effect of an automated telemedicine intervention on patients' time-to-hospitalisation. Methods: A total of 168 patients with a diagnosis of COPD in the past 24 months were enrolled to receive the intervention at a primary care clinic. The treatment group received daily phone messages from an automated system asking them to report if they were breathing better than, worse than, or the same as the day prior. Patients reported their breathing status by responding to the text message or call. If a patient reported breathing worse, an alert was sent directly to that patient's provider within the clinic. The control group received the same daily phone messages as the treatment group. However, no proactive breathing alerts were ever generated to the provider for these subjects. The primary outcome was the subjects' time-to-first-COPD-related hospitalisation following the start of messages. Results: The treatment group's time-to-hospitalisation was significantly different than the control group's with a hazard ratio of 2.36 (95% confidence interval 1.02–5.45, p  = 0.0443). The number needed-to-treat ratio was 8.62. Subject engagement consistently ranged between 60% and 75%. The treatment group received both proactive monitoring and follow-up care from the providers. Discussion: Active monitoring with provider feedback enables the detection of exacerbation events early enough for subjects to avoid admissions. The use of non-smartphone interventions reduces barriers to care presented by more complicated and expensive technologies. This intervention represents a simple, innovative, and inexpensive tool for improved COPD management.